PENERAPAN SQ3R BERBANTUNAN REKA CERITA GAMBAR UNTUK MENINGKATKAN PEMAHAMAN MEMBACA DAN HASIL BELAJAR SISWA - Aulia Rahmawati (Profesi Pendidikan Dasar, 2016)
The use of models and methods are very influential in the learning process. SDN 1 Bojong are still many students who do not understand the importance of reading, students assume that reading is boring, especially in subjects Indonesian. Implementation of action research conducted at SDN 1 Bojong to improve learning outcomes and students' reading comprehension in learning Indonesian. The study was conducted in four classes with the number of 27 students, 11 male and 16 female. After the study was conducted, the researchers obtained their learning outcomes and increase students' reading comprehension by applying SQ3R as assisted learning model Picture Maker Stories. The increase was generated in student achievement that can be greater than or equal to a predetermined KKM in Indonesian subjects, namely 75. In cycle 1 students who can achieve ≥75 value amounted to 17 out of 27 students or 63% of 100% and in the second cycle students who have achieved ≥75 value amounted to 21 out of 27 students or as much as 78% from 100%. Then saw an increase learning outcomes and students' reading comprehension of cycle 1 to cycle 2 and research using model SQ3R declared successful.